Estudio de caso – riesgo geológico. diseño y construcción del túnel de sumapaz (2018)
Between years 2006 to 2011, was realized the construction of the tunnel of the Sumapaz, located in the route that leads from Bogota to Girardot, builds singular of the contract of concession of third generation GG-040-2004, celebrated between the National Institute of Routes and the Society Concession freeway Bogotá Girardot S.A. The designs for the structuring of the project the company INGETEC S.A. realized them – BATEMAN INGENIERÍA Ltda. – PIV INGENIERÍA Ltda., establishing the amounts of work to execute, from which 10% of the majors were determined like risk geologic in charge of the concessionaire executed amounts and surpassed this top the recognition by extra charges on the part of the State. The concessionaire in agreement with the contractual power, contracted the nal design of the tunnel with the company PONCE DE LEÓN y CONSULTING ENGINEER ASOCIADOS S.A. – PL&A, with which the work was executed. The State through the National Infrastructure Agency, recognized and paid to the concessionaire the approximated sum of fifty-five billions of additional pesos, despite having counted with the designs of INGETEC and a margin of the ten percent (10%) in the established amounts of work like geologic risk in charge of the concessionaire.